DEVELOPMENT OF STUDENT LEARNING DISCIPLINES THROUGH THE ROLE OF THE SCHOOL ENVIRONMENT IN JAKARTA STATE HIGH SCHOOL STUDENTS - Nawang Wulansari; Mardi Mardi; Aditya Pratama (Yayasan Education and Social Center, 2023)
This study aims to determine the influence of learning motivation and self-efficacy on learning discipline with school environment moderation in class XI students of SMA Negeri 79 Jakarta. This research uses a quantitative approach with a questionnaire method. The total population in this study was 248, with a sample of 153 students using simple random sampling techniques. Data analysis is carried out by the SEM-PLS method. The results showed a positive and significant influence on learning motivation on learning discipline (r = 0.459, p-value = 0.000) and a positive and considerable influence of self-efficacy on learning discipline (r = 0.202, p-value = 0.00 6). The school environment does not moderate or does not affect the result of learning motivation on learning discipline (p-value = 0.184). The school environment does not make reasonable or does not affect the impact of self-efficacy on learning discipline (p-value = 0.506). These findings suggest that the school environment can not solely affect student learning discipline